1994
DOI: 10.1037/0022-3514.66.5.857
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity and positivity strivings in marriage and courtship.

Abstract: We proposed that married persons would want their spouses to see them as they saw themselves but that dating persons would want their relationship partners to evaluate them favorably. A survey of 176 married and dating couples tested these predictions. Just as married persons were most intimate with spouses whose evaluations verified their self-views, dating persons were most intimate with partners who evaluated them favorably. For married people with negative self-views, then, intimacy increased as their spou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
487
5
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 480 publications
(525 citation statements)
references
References 71 publications
24
487
5
1
Order By: Relevance
“…But married individuals are thought to resist such "groundless" flattery and insist that their partners see them as they see themselves (Swann et al, 1994). However, we did not find any evidence that being idealized detracts from satisfaction in marriage.…”
Section: Seeing What One's Partner Sees: the Benefits Of Shared Realicontrasting
confidence: 45%
See 2 more Smart Citations
“…But married individuals are thought to resist such "groundless" flattery and insist that their partners see them as they see themselves (Swann et al, 1994). However, we did not find any evidence that being idealized detracts from satisfaction in marriage.…”
Section: Seeing What One's Partner Sees: the Benefits Of Shared Realicontrasting
confidence: 45%
“…Perhaps self-verification is more important for the more objective, highly public attributes (e.g., physically attractive, musically skilled, athletic) examined by Swann et al (1994). Illusions, by contrast, may reap their greatest benefits when the criteria for possession of a particular attribute are more ambiguous, as may be the case with the more abstract, interpersonal qualities we examined (e.g., Dunning, Meyerowitz, & Holzberg, 1989;Goethals, Messick, & Allison, 1991).…”
Section: Seeing What One's Partner Sees: the Benefits Of Shared Realimentioning
confidence: 96%
See 1 more Smart Citation
“…Lemay and Dudley also demonstrated that inauthenticity is associated with decreased relationship satisfaction over time. The notion that people want to feel truly known by others is also well-documented (Swann, de la Ronde, & Hixon, 1994) and regulating what one does and does not communicate to an LSE may be cognitive costly (Vohs, Baumeister, & Ciarocco, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Vocal attractiveness provides social cues that help engage followers' implicit leadership theories. When cues like vocal attractiveness make leaders seem "leader-like" in the eyes of others, followers verify their role identities as followers, leading to greater trust, commitment, and emotional attachment to the leader (Burke & Stets 1999;Swann, De La Ronde and Hixon, 1994;Swann & Ely 1984;Turner 1968). Therefore vocal attractiveness should elicit personal reactions that reflect trust, commitment (willingness to accept influence, compliance, persuasion), and emotional attachment (liking).…”
Section: The Mediating Effect Of Personal Reactionsmentioning
confidence: 99%